Customer Satisfaction and Customer Loyalty Measurement in News Stand Settings - Janković, Sanja Raspor; Lanča, Stela (Oeconomica Jadertina, 2017)
The purpose of this study was to measure customer satisfaction and customer loyalty with news stand services, and to examine the relationship between the concepts of interest. The research was conducted on news stands in the city of Rijeka. Data were gathered using questionnaire. The questionnaire was created based on the studies conducted by Radman et al. (2002), Sinčić Ćorić, Vorkapić (2008) and Perić et al. (2010) and was adopted to the specific features of the present study. It consists of three parts. In first part customer satisfaction with news stand services was measured. Second par included variables for assessing customer loyalty. Third part consisted of respondents' demographic characteristics and buying habits in news stand. A total of 129 valid questionnaires were collected. Descriptive analysis and regression analyses were performed to analyze data. The findings showed high level of customer satisfaction and moderate level of customer loyalty. Furthermore, there is statistically significant relationship between attribute and overall customer satisfaction. The highest significant impact on overall customer satisfaction had staffs’ courtesy, product quality, and price. In addition, significant relationship was found between overall customer satisfaction and customer loyalty. The results of the present study may be useful to academics and practitioners in better understanding of customers’ attitudes and habits regarding the news stand services, in order to enhance the level of customer satisfaction and customer loyalty in this retail segment.
Keywords: customer satisfaction; customer loyalty; measurement; news stand; statistical analysis